2020
DOI: 10.1186/s13717-020-00226-9
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal changes of marshland and the driving forces in the Sanjiang Plain, Northeast China from 1980 to 2016

Abstract: Background Wetland loss is a global concern due to its enormous ecosystem services. Marshland, a typical natural wetland, which is concentrated in the Sanjiang Plain, has undergone dramatic loss in the last several decades. The spatiotemporal changes in marshland were studied based on Landsat images of the Sanjiang Plain from 1980 to 2016 with the land use maps in 1980, 1995, 2000, 2005, 2010, and 2016 using land use dynamic degree and landscape indices. The driving forces of marshland loss, including biophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…An increase in population will result in a reduction 1.020 -4 km 2 (or 102 m 2 ) of water bodies. This result is consistent with the reports by Wu et al [31], Li et al [30], UN [27], Li et al [29] and the WWAP [53]. The WWAP [53] reported that population growth has led to a tripling of water withdrawal over the last 50 years while the UN [27] also indicated that the population influences water resource change due to the wide range of human needs, includeing food production, industrial development and domestic demand.…”
Section: ) Panel Data Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…An increase in population will result in a reduction 1.020 -4 km 2 (or 102 m 2 ) of water bodies. This result is consistent with the reports by Wu et al [31], Li et al [30], UN [27], Li et al [29] and the WWAP [53]. The WWAP [53] reported that population growth has led to a tripling of water withdrawal over the last 50 years while the UN [27] also indicated that the population influences water resource change due to the wide range of human needs, includeing food production, industrial development and domestic demand.…”
Section: ) Panel Data Analysissupporting
confidence: 94%
“…According to Li et al [29], human activities and terrain conditions had a negative effect on the water body area in the Jing-Jin-Ji region while climate and soil properties had a positive effect. Li et al [30] also revealed that from 1980-2016, there was a drastic loss of marshland (65.7%) due to rapid paddy field expansion in the Sanjiang Plain, Northeast China, influenced mainly by biophysical, socio-economic and land management factors. Wu et al [31] reported a decreasing trend in water bodies and an increasing trend in built-up area at Longfeng Wetland Natural Reserve in Daqing city.…”
Section: Applied Environmental Researchmentioning
confidence: 99%
“…In the Songnen Plain, the expansion of agriculture during the past four decades has drastically lowered local groundwater levels, directly contributing to wetland shrinkage and salinization (Chen et al., 2018; Wang & Li, 2018). Similarly, in the Sanjiang Plain, rapid agricultural reclamation since the 1950s was identified as the primary driver of massive wetland loss, converting more than 70% of original wetlands into farmlands, while the contributions of climate change have been found growing (Li et al., 2020; Yan & Zhang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With the change of climate, planting systems and cultivated land layout in China vary in their regional climate adaptability, and the expansion of paddy fields in the cultivated land is prominent. Northeast China is a typical area of paddy field expansion among cultivated land (Ye et al, 2009;Li et al, 2020), and climate change is an important reason for the development of paddy fields in that area. However, the response characteristics of changed cultivated land use and distribution under different climatic factors and trends remain unclear, and the climatic basis for the change of both paddy field and dry land also needs more research.…”
Section: Introductionmentioning
confidence: 99%